J.O. Francis, realist drama and ethics : culture, place and nation. - Von Rothkirch, Alyce (Writing Wales in English., 2014)
Developing an ethical literary theory of place, this book rediscovers and re-evaluates the work of the Welsh dramatist J.O. Francis, placing his work within the context of the vibrant amateur dramatic scene of the early twentieth century.